Early posttransplant nephrotic range proteinuria as a presenting feature of minimal change disease and acute T cell-mediated rejection - A. Nongnuch (2018)
Early-onset nephrotic range proteinuria is an extremely rare presentation of an acute rejection episode. Herein, we have reported a patient who developed nephrotic range proteinuria 7 days after receiving a renal allograft from his sister despite minor changes in serum creatinine levels. A kidney biopsy spcimen revealed a T cell-mediated acute rejection process concomitant with minimal change disease (MCD). Proteinuria and renal dysfunction improved dramatically in response to corticosteroids. The possibility of acute cellular rejection and coexisting MCD should be considered in patients with early posttransplantation nephrosis and normal serum creatinine levels. The coexistence of these entities provides support for the role of T cells in the pathogenesis of MCD. © 2012 Elsevier Inc. © 2014 by Elsevier Inc. All rights reserved.